INVERSE COMPUTATIONAL DETERMINATION OF JOHNSON-COOK PARAMETERS USING THE SHPB TEST APPARATUS - Anja Mauko; Branko Nečemer; Zoran Ren (Acta Polytechnica CTU Proceedings)
The paper describes determination of the material parameters of the Johnson-Cook constitutive model of steel S235 JR sample material by applying the inverse computational methodology using the digital twin model of the SHPB. A quasi-static tensile testing of bulk material was conducted ﬁrst to determine the base material parameters. This was followed by dynamic impact testing at two diﬀerent strain rates using the SHPB. A digital twin computational model was built next in the LS-Dyna explicit ﬁnite element system to carry out the necessary computer simulations of the SHPB test. The inverse determination of strain hardening material parameter of Johnson-Cook model was done by using the Nelder-Mead simplex optimisation by comparing the measured and computed stress to time signals on incident and transmission bars. The obtained Johnson-Cook material parameters much better describe the sample material behaviour at very high strain-rates in computational simulations, if compared to the parameters derived by the classic, one-dimensional wave propagation Hopkinson procedure.